2009
DOI: 10.1002/cpp.608
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of self‐complexity in individuals experiencing auditory hallucinations

Abstract: Linville's self-complexity (SC) theory suggests that reduced SC exacerbates the effects of stress, thereby creating a vulnerability to psychopathology. This exploratory study investigated SC in individuals experiencing auditory hallucinations. Twenty-two clinical participants experiencing auditory hallucinations were recruited from inpatient and outpatient services. Twenty-two control participants, matched on age and gender, were recruited from non-clinical settings. All participants completed a card sort task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Swarbrick, Bentall, and Wittkowski (2006) found that individuals with paranoid delusions had lower levels of self-complexity compared with a non-clinical control group. Bell and Wittkowski (2009) instead found no such relation when comparing a sample of persons with auditory hallucinations to healthy controls. One possibility explored by Bell and Wittkowski is that the relevant factor was not the overall multiplicity of the self, but the presence of a nuanced view of either positive or negative aspects of the self.…”
mentioning
confidence: 84%
“…Swarbrick, Bentall, and Wittkowski (2006) found that individuals with paranoid delusions had lower levels of self-complexity compared with a non-clinical control group. Bell and Wittkowski (2009) instead found no such relation when comparing a sample of persons with auditory hallucinations to healthy controls. One possibility explored by Bell and Wittkowski is that the relevant factor was not the overall multiplicity of the self, but the presence of a nuanced view of either positive or negative aspects of the self.…”
mentioning
confidence: 84%
“…In individuals with a diagnosis of schizophrenia, low self-concept clarity has been found to predict higher levels of positive symptoms, lower subjective quality of life and increased risk of perceived exposure to stigmatization ( Weinberg et al, 2012 ; Noyman-Veksler et al, 2013 ). In relation to voice hearing specifically, Bell and Wittkowski (2009) found evidence for reduced positive self complexity in voice hearers, and an association between higher positive self complexity and increased psychological wellbeing. However, at odds with the predictions of early dialogical theories, a recent study found that the phenomenology of inner speech in voice hearers does not differ significantly from that of non-clinical participants ( Langdon et al, 2009 ).…”
Section: Bringing the “Self” Into Focus: A Phenomenologically-informementioning
confidence: 95%
“…a selfconcept which lacks integration) is an important precursor to the development of psychological problems (Lutz and Ross, 2003). It has been suggested that a damaged self-concept may confer risk of psychosis (Bell and Wittkowski, 2009). Indeed, phenomenological approaches have implicated a disturbed basic sense of self in prodromal psychosis (Nelson et al, 2009), and evidence suggests that a lack of unity within the self-concept structure may be related to psychosis-like experiences (Preston, 2008).…”
Section: Introductionmentioning
confidence: 99%